Analisis Pendapatan dan Kelayakan Usaha Minyak Nilam di Kecamatan Kluet Tengah Kabupaten Aceh Selatan - Jumadi Ahmad; Firdaus Firdaus; Syarifuddin Syarifuddin (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
Patchouli plant is a plant that produces patchouli oil. Patchouli oil refinery is a potential business to be developed because Indonesia has a tropical climate that is suitable for planting patchouli plants. And businesses that can utilize local resources and are oriented towards the export market. The purpose of this study was to determine the amount of income derived from the patchouli oil business and to analyze the feasibility of the patchouli oil business in Kluet Tengah District, South Aceh Regency. The research method used survey method. The sampling technique is "Simple Random Sampling" of 10% with a total sample of 23 farmers. The data analysis model used is income analysis, feasibility analysis of R/C Ratio and feasibility analysis of Break Event Point (BEP). The results showed that the average income received by patchouli oil farmers in Kluet Tengah District, South Aceh Regency was Rp. 4.140.614/year with an average income per hectare of Rp.14.781.991,98/year. The Revenue Cost Ratio of patchouli oil is worth pursuing, because it produces a comparison of total revenue with a total cost that is greater than one, which has a number of 1,40 > 1. In other words, an R/C value of 1,40 means that for every Rp. 100 costs incurred, then farming Patchouli oil earns Rp. 140. BEP (Break Event Point) per kilogram of patchouli oil, namely 4,16 kg of patchouli oil and BEP in rupiah sales of Rp. 2.196.078,44. So patchouli oil farming in Kluet Tengah District, South Aceh Regency is said to be profitable, because the yield values obtained exceed the BEP values. The average amount of patchouli production obtained was 27,2173913 kg and sales proceeds (receipts) were Rp. 14.425,217,4